2013
DOI: 10.1039/c3cc44557g
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of photo-cleavable polymers via Passerini reaction

Abstract: Passerini three-component reaction and multicomponent polymerization (MCP) were demonstrated to be facile methods for the preparation of photo-cleavable polymers, photo- and redox-dually cleavable polymers, as well as block copolymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 44 publications
0
74
0
Order By: Relevance
“…In our previous reports, we found that the Passerini MCP of a diisocyanide, a dicarboxylic acid and an o-nitrobenzaldehyde could efficiently generate UV degradable polymers, demonstrating that onitrobenzaldehyde is a highly reactive aldehyde towards this polymerization [59,60]. To examine whether the catechol group is compatible with this polymerization process, we first carried out the model Passerini reaction of 3-(3,4-dihydroxyphenyl) propionic acid, 5-ethoxy-2-nitrobenzaldehyde and tert-butyl isocyanide.…”
Section: Polymer Synthesis and Characterizationmentioning
confidence: 85%
See 1 more Smart Citation
“…In our previous reports, we found that the Passerini MCP of a diisocyanide, a dicarboxylic acid and an o-nitrobenzaldehyde could efficiently generate UV degradable polymers, demonstrating that onitrobenzaldehyde is a highly reactive aldehyde towards this polymerization [59,60]. To examine whether the catechol group is compatible with this polymerization process, we first carried out the model Passerini reaction of 3-(3,4-dihydroxyphenyl) propionic acid, 5-ethoxy-2-nitrobenzaldehyde and tert-butyl isocyanide.…”
Section: Polymer Synthesis and Characterizationmentioning
confidence: 85%
“…Our recent works demonstrated that the multicomponent polymerization (MCP) of a diisocyanide, a dicarboxylic acid and an o-nitrobenzaldehyde was a straightforward way to synthesize photocleavable polymers [59,60]. The key point was the in-situ formed o-nitrobenzyl ester linkage in the polymer main chain, this linkage can be cleaved upon UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, polymer P8 has oligo(ethylene oxide)s as side groups, it may be a new type of thermoresponsive polymer, which may find applications in biomedical science . Polymer P9 contains o ‐nitrobenzyl ester moieties in the main chain, and this type of polymer has been proven to be a UV‐cleavable polymer, which may find applications in cell patterns and drug delivery …”
Section: Resultsmentioning
confidence: 99%
“…MCRs are those reactions to combine more than two reactants in a sequential manner to give highly selective products that retain majority of the atoms of the starting materials. Although known for over 150 years in organic chemistry, only recently, with Meier's introducing tri-component Passerini reaction into polymer chemistry 21,22 , a series of multicomponent reactions (MCRs) such as Ugi reaction, Biginelli reaction, Kabachnik-Fields (KF) reaction, thiolactone-based reactions etc., have been reconsidered from the perspective of polymer chemistry and ultilized to prepare delicated polymers [23][24][25] . Different from traditional two-component coupling reactions (click reactions etc.…”
Section: Introductionmentioning
confidence: 99%